Reading Habits of Students of Infant Jesus College of Engineering - Thoothukudi - Balasubramanian, P. (Journal of Information and Knowledge, 2014)
This article attempts to investigate into the reading habits of college students by studying about their use of college library. In a library and information system, the essential components are documents, users and librarians. Users’ attitudes are essential considerations in the design of the library system.